Human Endogenous Retrovirus W Activity in Cartilage of Osteoarthritis Patients. (22nd July 2014) - Bendiksen, Signy; Martinez-Zubiavrra, Inigo; Tümmler, Conny; Knutsen, Gunnar; Elvenes, Jan; Olsen, Elisabeth; Olsen, Randi; Moens, Ugo
Abstract : The etiology of viruses in osteoarthritis remains controversial because the prevalence of viral nucleic acid sequences in peripheral blood or synovial fluid from osteoarthritis patients and that in healthy control subjects are similar. Until now the presence of virus has not been analyzed in cartilage. We screened cartilage and chondrocytes from advanced and non-/early osteoarthritis patients for parvovirus B19, herpes simplex virus-1, Epstein Barr virus, cytomegalovirus, human herpes virus-6, hepatitis C virus, and human endogenous retroviruses transcripts. Endogenous retroviruses transcripts, but none of the other viruses, were detected in 15 out the 17 patients. Sequencing identified the virus as HERV-WE1 and E2. HERV-W activity was confirmed by high expression levels of syncytin, dsRNA, virus budding, and the presence of virus-like particles in all advanced osteoarthritis cartilages examined. Low levels of HERV-WE1, but not E2 envelope RNA, were observed in 3 out of 8 non-/early osteoarthritis patients, while only 3 out of 7 chondrocytes cultures displayed low levels of syncytin, and just one was positive for virus-like particles. This study demonstrates for the first time activation of HERV-W in cartilage of osteoarthritis patients; however, a causative role for HERV-W in development or deterioration of the disease remains to be proven.